Microeconomics - Besanko, David; Braeutigam, Ronald (New jersey, 2011)
After many years of experience teaching microeconomics at the undergraduate and MBA levels, we have concluded that the most effective way to teach it is to present the content with a variety of engaging applications, coupled with an ample number of practice problems and exercises. The applications ground the theory in the real world, and the exercises and problems sets enable students to master the tools of economic analysis and make them their own. The applications and the problems are combined with verbal intu-ition and graphs, so that they are reinforced and amplified. This approach enables students to see clearly the interplay of key concepts, to thoroughly grasp these concepts through abundant practice, and to see how they apply in actual markets and business firms.
Keywords: Microeconomics